2017
DOI: 10.4062/biomolther.2017.089
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Glycine and Leucine Dipeptides Improves Skin Hydration and Elasticity in UVB-Irradiated Hairless Mice

Abstract: Placenta is a special organ that contains many nutrients such as growth factors, minerals, and bioactive peptides. Dipeptides of glycine and leucine are major components of porcine placenta extracts (PPE) that has been used as an alternative of human placenta extracts. In this study, we investigated whether major peptides of PPE, Glycyl-L-Leucine (Gly-Leu), L-Leucyl-Glycine (Leu-Gly), and L-Leucyl-L-Leucine (Leu-Leu), affect skin hydration and elasticity in vitro and in vivo. We found that Gly-Leu and Leu-Gly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…According to reports, HAS2 can synthesize HA. It has been previously reported that UV exposure induced loss of HA and inhibition of HAS in skin 36 . It has been suggested that HA was involved in the natural responses of epidermal in wound‐healed and barrier recovery in AD, including proliferation and migration of keratinocyte 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reports, HAS2 can synthesize HA. It has been previously reported that UV exposure induced loss of HA and inhibition of HAS in skin 36 . It has been suggested that HA was involved in the natural responses of epidermal in wound‐healed and barrier recovery in AD, including proliferation and migration of keratinocyte 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that UV exposure induced loss of HA and inhibition of HAS in skin. 36 It has been suggested that HA was involved in the natural responses of epidermal in wound-healed and barrier recovery in AD, including proliferation and migration of keratinocyte. 37 It has been shown that HA bound to its best-characterized cell surface receptor, CD44, induced LB (lamellar body) formation and secretion, and enhanced expressions of keratinocyte differentiation markers including K10, profilaggrin, which was very important to skin barrier repair and maintains skin hydration.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that dermal fibroblasts exist in placenta extract [ 11 , 12 ], whereas other investigations demonstrated that dermal fibroblasts enable the synthesis of collagen, elastic fibers, and dermal hyaluronic acid [ 9 , 10 ]. Although the internal mechanism of oral supplementation with porcine placenta has been unclear, a previous study reported that major porcine placenta peptides in a living organism: Glycyl-L-Leucine (Gly-Leu), L-Leucyl-Glycine (Leu-Gly), and L-Leucyl-L-Leucine (Leu-Leu), affect skin hydration and elasticity in in vitro and in vivo studies [ 42 ]. Our findings are consistent with those of previous investigations that explain the placenta extract effects with several potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Skin aging is also associated with skin water loss, the main factor being hyaluronic acid (HA), an extracellular matrix molecule [16]. Several factors control skin moisture and elasticity, including HA and elastic fibers, which regulate skin tissue elasticity and resilience [17]. Enzymes such as HA synthases (Has) synthesize HA, and Has2 expression is differentially upregulated by TGF-β1 in the dermis and epidermis [18].…”
Section: Introductionmentioning
confidence: 99%